Contemporary Economic Sociology: Towards Theoretical Synthesis of Sociological and Economic Knowledge - Nonchev, Andrey (UNWE Yearbook, 2020)
The paper examines the complex and contradictory relationships between sociological and economic science in the decades of their coexistence. Emphasis is placed on the heuristic potential of the more intensive interaction of sociological and economic analysis since the 70s of the last century. The article discusses three methodological approaches within which the sociological and economic perspectives intersects - neoinstitutionalism, social network analysis, economic and sociological theories of rational choice. Some key ideas of contemporary economic sociology aimed at seeking a theoretical synthesis between sociological and economic knowledge are also outlined. In conclusion, comments are made on some global trends of modernity, which require the development and upgrading of the theoretical principles of the new economic sociology.
Keywords: New economic sociology; Neoinstitutionalism; Social network analysis; Theories of rational choice